Efficacy of combined liposomal quercetin and yellow sweet clover aqueous extract in moderate blunt trauma to the eye in rabbits - O.P. Sotnikova; N.O. Chudniavtseva; G.S. Fesiunova; Yu. M. Rodina; T.D.Lotosh; G.B.Abramova; G.M.Tsybuliak (Ukrainian Society of Ophthalmologists, 2018)
Introduction. Despite the numerous experimental and clinical investigations, the development of new rational treatments for blunt trauma to the eye remains a topical issue. Purpose. To study the efficacy of a combined use of liposomal Lipoflavon instillations and periocular injections of a yellow sweet clover aqueous extract for moderate blunt trauma to the eye in experiment. Material and Methods. Moderate blunt trauma (2 to 3 Nm) was accomplished transpalpebrally using a special device in 15 eyes of 30 rabbits. The animals were divided equally into two Study groups and Control Group: Study group 1, instillations of Lipoflavon and subconjunctival injections of a yellow sweet clover aqueous extract; Group 2, instillations of Lipoflavon and parabulbar injections of a yellow sweet clover aqueous extract; Control Group, untreated simulated pathology as controls. A degree of inflammatory response of the eye, a condition of the cornea, and hemorrhages into the anterior chamber were assessed using a scoring system which had been improved by us. Coagulogram characteristics including thrombin time (TT), prothrombin time (PTT), activated partial thromboplastin time (APTT), and fibrinogen were determined. Results. Lipoflavon instillations and periocular injections of a yellow sweet clover aqueous extract for treating the eyes after moderate blunt were proved to have a pronounced therapeutic effect as compared to control, based on the clinical signs of the total post-traumatic response of the eye. The total response of the eye to blunt trauma was slightly decreased in the group receiving parabulbar injections of a yellow sweet clover aqueous extract as compared to the group receiving subconjunctival injections at Days 3 and 7 of the experiment. A combined use of Lipoflavon eye drops and periocular yellow sweet clover injections in treating the eyes after moderate blunt trauma results in changes in coagulation hemostasis indices towards hypocoagulation, which is evidenced by an increase in PTT averagely by 43% and a decrease of the fibrinogen level averagely by 25%. Conclusions. Lipoflavon instillations in combination with periocular yellow sweet clover injections for experimental blunt trauma of moderate severity have a pronounced therapeutic effect comparing to untreated controls and result in changes in coagulation hemostasis indices towards hypocoagulation.